Pulse width modulation in a autonomous voltage inverter at identification of parametersthree-phase asynchronous motor - V. G. Makarov; Y. A. Yakovlev; V. N. Khannanova (Известия высших учебных заведений: Проблемы энергетики, 2017)
The expediency of using the mathematical description of the generalized electric machine in the identification of the parameters of three phase induction motor. However, the implementation of the algorithm pulse width modulation in three-phase autonomous voltage inverter necessary to make the transition from the variables in the coordinate system of the generalized electrical machines to the variables of the three-phase system. The necessary transformations, the laws of change of the phase voltages of the inverter are carried out. With the help of computer simulation and experimental studies it was shown that the necessary shape of the phase voltages can be implemented in the autonomous voltage inverter with pulse width modulation.